2015
DOI: 10.5430/mos.v2n2p45
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Career Paths of Athletic Administrators in NCAA-Member Institutions

Abstract: Very little is known about the educational and experiential backgrounds of athletic administrators. The purpose of this study was to investigate these backgrounds in collegiate athletic departments. Results indicated significant differences across the three National Collegiate Athletic Association divisions and between males and females related to the educational and experiential backgrounds of athletic administrators, exclusive of athletic directors. Division I administrators were significantly more likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The research into the career patterns of sports manager has been limited and fragmented, concerning mainly three categories of individuals: collegiate athletic administrators in the US, women and ethnic minorities, and sports management alumni. The results of these studies indicate three phenomena: (1) a trend towards professionalisation and more business-oriented backgrounds and pathways in collegiate sports organisations that once used to rely solely on athletic and coaching experience (Fitzgerald et al , 1994; Hardin et al , 2013; Lumpkin et al , 2015); (2) the underrepresentation of women and ethnic minorities in sports administration and their non-normative career patterns (Armstrong, 2015; Bower and Hums, 2013; M'mbaha and Chepyator-Thomson, 2019); (3) quite complex and heterogeneous initial pathways in the sports industry where there are challenges of getting a first job and working-up through the industry, with no clear dominance of either traditional or new career types (McNiff, 2013; Minten and Forsyth, 2014; Schwab et al , 2015). Most of these studies used qualitative methods and as such did not evaluate the magnitude of the phenomena.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research into the career patterns of sports manager has been limited and fragmented, concerning mainly three categories of individuals: collegiate athletic administrators in the US, women and ethnic minorities, and sports management alumni. The results of these studies indicate three phenomena: (1) a trend towards professionalisation and more business-oriented backgrounds and pathways in collegiate sports organisations that once used to rely solely on athletic and coaching experience (Fitzgerald et al , 1994; Hardin et al , 2013; Lumpkin et al , 2015); (2) the underrepresentation of women and ethnic minorities in sports administration and their non-normative career patterns (Armstrong, 2015; Bower and Hums, 2013; M'mbaha and Chepyator-Thomson, 2019); (3) quite complex and heterogeneous initial pathways in the sports industry where there are challenges of getting a first job and working-up through the industry, with no clear dominance of either traditional or new career types (McNiff, 2013; Minten and Forsyth, 2014; Schwab et al , 2015). Most of these studies used qualitative methods and as such did not evaluate the magnitude of the phenomena.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Division I programs are the largest in both of these categories and require considerable infrastructures to support teams and athletes, so we expected they would also employ the most mid‐level staff members. As the remainder of this chapter will illustrate, the distribution of mid‐level administrators varies quite a bit according to competitive Division, as do their backgrounds, job responsibilities, and careers (Lumpkin, Achen, & Hyland, 2015; Weaver & Chelladurai, 2002).…”
Section: Distribution Of Mid‐level Positions Across College Sports Prmentioning
confidence: 99%
“…Research by Lumpkin et al. (2015) indicated that former high school or college coaches made up 47% of Division III mid‐level administrators, although they were only 19% of Division I and 36% of Division II.…”
Section: Key Factors Associated With Mid‐level Career Success In Intementioning
confidence: 99%
See 2 more Smart Citations